THE INFLUENCE OF SERVICE QUALITY, PRICE, AND BRAND AMBASSADOR ON TOKOPEDIA ONLINESHOP PURCHASE DECISIONS - Avif Hanif Fadlun; Awang Darmawan Putra; Muhamad Azis Dirdaus (Jurnal Ilmiah Global Education, 2023)
Previous studies reported inconsistent results about the effect of service quality and price on consumers' purchasing decisions. However, no study has been done about the impact of service quality, price, and brand ambassador on purchasing decisions of Tokopedia customers. This study aimed to evaluate the effect of service quality, price, and brand ambassador on buying decisions of Tokopedia customers. This study used a survey method with simple random sampling during the sample determination of Tokopedia customers. The 91 customers were given 44 questions with five alternative answers. The results showed that purchasing decision of Tokopedia customers was positively affected by service quality and brand ambassador. In contrast, the purchasing decision was negatively affected by product price. Therefore, purchasing decision made by Tokopedia customers was affected by service quality, price, and brand ambassador. Further studies are needed to obtain a general conclusion about the shopping behaviour of online shop customers in Indonesia.